2016
DOI: 10.1007/s10916-016-0634-y
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Based on Fuzzy Aggregation Operators for Medical Diagnosis from Dental X-ray images

Abstract: Medical diagnosis is considered as an important step in dentistry treatment which assists clinicians to give their decision about diseases of a patient. It has been affirmed that the accuracy of medical diagnosis, which is much influenced by the clinicians' experience and knowledge, plays an important role to effective treatment therapies. In this paper, we propose a novel decision making method based on fuzzy aggregation operators for medical diagnosis from dental X-Ray images. It firstly divides a dental X-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Modified Hopfield neural network [26] or advanced fuzzy decision making [28] would be the solution to our problem, which warrants further research. Moreover, similar to the research in [29,30], the proposed algorithms need to be applied to different datasets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified Hopfield neural network [26] or advanced fuzzy decision making [28] would be the solution to our problem, which warrants further research. Moreover, similar to the research in [29,30], the proposed algorithms need to be applied to different datasets.…”
Section: Discussionmentioning
confidence: 99%
“…In future works, we will make the implementations on a wider range of different, complex dental image datasets to verify the suitability of this algorithm. Other integrations between deep learning and fuzzy computing in our previous studies [28,31,32] would be vital for favorable outcomes in upcoming research.…”
Section: Discussionmentioning
confidence: 99%
“…Using the existing system (i.e., sparse representation), the accuracy of the HR image was 80%, but using the proposed method (global face sparse representation), the accuracy of the HR image was 85-90%. In the future, we will study various methods [32][33][34][35][36][37][38][39][40][41][42][43] and enhance the algorithm on posed face images. The computational complexity of the proposed system was analyzed using the big oh notation O n 2 K M , for the face hallucination methodology.…”
Section: Discussionmentioning
confidence: 99%
“…where R a and R b are random numbers having the range [0,1] and X r,j is the knowledge (position) value of the chosen individual. From Equations (2) and 3, it can be observed that the implementation of the SGO algorithm is simple compared to other algorithms existing in the image processing domain [40][41][42][43][44][45][46][47][48]. The steps of the standard SGO algorithm can be described as in Algorithm 1.…”
Section: Social Group Optimizationmentioning
confidence: 99%